Novel Control System Strategy for the Catalytic Oxidation of VOCs with Heat Recovery - Miranda, Angel Federico (2023)
A theoretical study of the dynamic closed-loop behaviour of a reactor/feed-effluent heat exchanger (FEHE)/furnace system for the catalytic combustion of volatile organic compounds (VOCs) is presented. A 1D pseudohomogeneous plug-flow model is proposed to simulate the non-steadystate operation of the monolith reactor and the FEHE, while the furnace behaviour is described by means of a heterogeneous model of lumped parameters. Positive energy feedback is a source of instability that leads to strong thermal oscillations (limit cycles) and may cause damage to the equipment and sintering of the catalyst. The design of a robust and flexible control system and an efficient control strategy are, therefore, required to ensure safe and stable operation. The response of the system under three different control strategies to the most frequent disturbance variables—the feed flowrate (FV0 ) and feed concentration of VOCs (C0Et)—was evaluated. One of the control strategies consisted of a single-loop feedback system with servomechanism changes in the reactor inlet temperature (T0 ) that manipulated the bypass valve and, sequentially, the natural gas flowrate in the furnace (FNG). This approach made it possible to meet the control objective (reducing VOCs) without losing controllability and while minimizing the use of external fuel.